Logistics Management and the Performance of Manufacturing Firms in Selected States of Northern Nigeria - Umar, Adeiza Muazu (International Journal of Engineering and Management Research, 2019)
The study examined the role of logistics in manufacturing firms’ performance in some states in Northern Nigeria. A firm-level survey was conducted in a cross-sectional examination of members of the Manufacturers Association of Nigeria (MAN), with a sample of 144 firms. The study was underpinned by the resource-based theory, and data was analyzed using multiple regression analysis through the partial least squares structural equation modeling (PLS-SEM). It was discovered that both inbound and outbound logistics have positive relationships with performance. However, the relationship between outbound logistics and performance was not significant. The findings implies that managers of manufacturing firms cannot entirely rely on the contributions of logistics to enhance performance. It was therefore recommended that management in the manufacturing sector could find ways of improving those outbound activities they perform; contemplate involving drivers, such as information technology to boost performance; and consider outsourcing those outbound activities.